SUPERVISI BERBASIS KOLABORATIF SEBAGAI UPAYA PENINGKATAN KUALITAS PEMBELAJARAN - Hariadi, Hariadi; Akbar, Ali; Supriandi, Supriandi; Herman, Herman; Rawati, Rawati (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
ABSTRACT This study discusses collaborative supervision as a means of improving educational quality at SMP Negeri 27 Makassar. The author formulates a sub-problem concerning how collaborative supervision is implemented at SMP Negeri 27 Makassar. This research employs a qualitative design with a phenomenological approach to gain a comprehensive understanding of the situation from the perspectives of the subjects involved in supervision activities, namely the principal, teachers, and school supervisors. Data were collected through documentation, interviews, and observations. The data analysis techniques included data reduction, comparative analysis, and conclusion drawing. The results of the study indicate that the principal plays a role as a facilitator in organizing supervision and in providing observation instruments collaboratively with teachers and school supervisors. School supervisors also participate by providing guidance and support related to the supervision program, which helps strengthen relationships between teachers and school leadership. Supervision results are then used to formulate improvement strategies. The improvement steps identified include enhancing teachers’ competencies in digital literacy for instructional presentation, developing teachers’ competencies in their respective fields of expertise, and fostering collaboration within subject-area groups for the development of teaching materials. ABSTRAK Penelitian ini membahas supervisi kolaboratif sebagai sarana peningkatan mutu pendidikan di SMP Negeri 27 Makassar. Penulis kemudian membagi ke dalam submasalah, yaitu bagaimana supervisi kolaboratif di implementasikan di SMP Negeri 27 Makassar. Jenis penelitian ini merupakan kualitatif dengan pendekatan fenomenalogi untuk memahami keadaan secara menyeluruh dari sudut pandang subjek yang terlibat dalam kegiatan supervisi, yaitu kepala sekolah, guru, dan pengawas sekolah. Metode pengumpulan data lainnya yang digunakan adalah dokumentasi, wawancara, dan observasi. Teknik analisis data, penggalian data, teknik analisis komparatif, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Kepala sekolah berperan sebagai fasilitator dalam mengorganisir supervisi, menyediakan alat observasi bersama guru, dan pengawas sekolah. Pengawas sekolah turut serta memberikan bimbingan dan dukungan terkait program supervisi akan membantu memperkuat hubungan antara guru dan pimpinan. Hasil supervisi dan merumuskan langkah-langkah perbaikan. Adapun langkah perbaikan yang dihasilkan ialah pengembangan kompetensi guru dalam penguasaan digitalisasi dalam penyajian materi pengajaran, pengembangan kompetensi guru di masing-masing bidang keahlian, membangun kerjasama dalam rumpun keilmuan dalam pembuatan bahan ajar.